2020
DOI: 10.1007/s10904-020-01674-8
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Nanomaterials in Food Packaging and its Advanced Future Prospects

Abstract: Biopolymers have been used in packaged foods to tackle environmental hazards due to their biodegradability and non-toxic nature. In addition to these merits, they have also several demerits such as poor mechanical properties and low resistance towards water. Nanomaterials have attracted great interest in recent years due to their phenomenal properties that makes them precedent in applications for food packaging as they enhance the mechanical, thermal and gas barriers properties, without compromising with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(96 citation statements)
references
References 113 publications
0
87
0
Order By: Relevance
“…In addition, these nanoparticles have been recently approved by the European Food Safety Authority (EFSA) to be used as a transparent ultraviolet (UV) light absorber in polyolefins for food packaging applications [38]. The addition of ZnO-NPs to polymer matrices such as polyurethane and chitosan has been reported to decrease water vapor and oxygen transmission rate compared to the neat films [39] while some authors reported the use of ZnO-NPs in modified atmosphere packaging (MAP) [40]. Few reports have been found combining ZnO-NPs and pectin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these nanoparticles have been recently approved by the European Food Safety Authority (EFSA) to be used as a transparent ultraviolet (UV) light absorber in polyolefins for food packaging applications [38]. The addition of ZnO-NPs to polymer matrices such as polyurethane and chitosan has been reported to decrease water vapor and oxygen transmission rate compared to the neat films [39] while some authors reported the use of ZnO-NPs in modified atmosphere packaging (MAP) [40]. Few reports have been found combining ZnO-NPs and pectin.…”
Section: Introductionmentioning
confidence: 99%
“…nanoparticles are due to their high antimicrobial activity very suitable agents for antimicrobial active packaging systems [ 69 ]. TiO 2 nanoparticles as non-toxic to human body and approved as a food additive and for food contact material are often applied to food packaging [ 70 ]. Further studies on the post digestion and adsorption effect to the body are required to ensure its safe use in the food industry [ 71 ].…”
Section: Food Packagingmentioning
confidence: 99%
“…However, the toxicity seems to depend on the type and size of the nanoparticles [ 216 ]. Side effects caused by nanoparticles exposure include the formation of reactive oxygen species (ROS), protein denaturation, mitochondrial disorder, and phagocytosis dysfunction [ 70 ]. A potential concern should be focused on the migration of nanomaterials from the packaging or the sensing element inside the packaging into the food.…”
Section: Safety and Environmental Concerns Of (Bio)nanotechnology mentioning
confidence: 99%
“…This is a form of wet‐chemical procedure that involves a chemical solution that serves as a precursor to link participating particles. Sol–gel synthesis of nanoparticles is achieved by metallic oxides and chlorides that are applied as components (Abdelhalim, Abdellah, Scarpa, & Lugli, 2014; Chaudhary, Fatima, & Kumar, 2020). The metallic oxides and chlorides are mixed in a chemical solution by spinning, stirring, and sonication to disperse the solid phase in the liquid phase (Chaudhary et al, 2020).…”
Section: Functions Of Packaging In Food Processingmentioning
confidence: 99%